FLUX-CREEP IN HIGH-TEMPERATURE SUPERCONDUCTORS IN LOW FIELDS AT 77K - Jones, J; Wilshaw, P; Dewhughes, D; Johnson, K (1992)
A technique that allows the flux-creep of bulk superconductors to be studied has been developed. This technique has been applied to the measurement of flux-creep in samples of lead doped BiSCCO 2223 that have undergone a variety of processing routes.